The outcome of trachomatous trichiasis surgery in Ethiopia: risk factors for recurrence. - Saul N Rajak; Esmael Habtamu; Helen A Weiss; Amir B Kello; Bayeh Abera; Mulat Zerihun; Teshome Gebre; Clare E Gilbert; Peng T Khaw; Paul M Emerson; Matthew J Burton (PLoS Neglected Tropical Diseases)
Background Over 1.2 million people are blind from trachomatous trichiasis (TT). Lid rotation surgery is the mainstay of treatment, but recurrence rates can be high. We investigated the outcomes (recurrence rates and other complications) of posterior lamellar tarsal rotation (PLTR) surgery, one of the two most widely practised TT procedures in endemic settings. Methodology/principal findings We conducted a two-year follow-up study of 1300 participants who had PLTR surgery, conducted by one of five TT nurse surgeons. None had previously undergone TT surgery. All participants received a detailed trachoma eye examination at baseline and 6, 12, 18 and 24 months post-operatively. The study investigated the recurrence rates, other complications and factors associated with recurrence. Recurrence occurred in 207/635 (32.6%) and 108/641 (16.9%) of participants with pre-operative major (>5 trichiatic lashes) and minor (<5 lashes) TT respectively. Of the 315 recurrences, 42/315 (3.3% overall) had >5 lashes (major recurrence). Recurrence was greatest in the first six months after surgery: 172 cases (55%) occurring in this period. Recurrence was associated with major TT pre-operatively (OR 2.39, 95% CI 1.83-3.11), pre-operative entropic lashes compared to misdirected/metaplastic lashes (OR 1.99, 95% CI 1.23-3.20), age over 40 years (OR 1.59, 95% CI 1.14-2.20) and specific surgeons (surgeon recurrence risk range: 18%-53%). Granuloma occurred in 69 (5.7%) and notching in 156 (13.0%). Conclusions/significance Risk of recurrence is high despite high volume, highly trained surgeons. However, the vast majority are minor recurrences, which may not have significant corneal or visual consequences. Inter-surgeon variation in recurrence is concerning; surgical technique, training and immediate post-operative lid position require further investigation.